Tracking shoreline erosion of "at risk" coastal archaeology: the example of ancient Siraf (Iran, Persian Gulf). (December 2018) - Pourkerman, Majid; Marriner, Nick; Morhange, Christophe; Djamali, Morteza; Amjadi, Sedighe; Lahijani, Hamid; Beni, Abdolmajid Naderi; Vacchi, Matteo; Tofighian, Hossein; Shah-Hoesseini, Majid
Abstract: Successful heritage management requires a robust comprehension of the threats facing archaeological sites, at both current and future timescales. Siraf, on the Persian Gulf of Iran, is a site of national and international importance whose history stretches back to the Sassanid period (224–652 AD). In the present context of global change (drought and relative sea-level rise) and anthropogenic impacts (coastal artificialization and reduced sediment supply), the city's waterfront archaeology is undergoing significant erosion. Nonetheless, at present, the processes leading to the loss of Siraf's in situ archaeological remains are still poorly understood, including the rates, timing and drivers of coastal erosion. Here we use Landsat images to monitor shoreline changes along the Siraf coastline between 1973 and 2016. We spatially quantify the causes and impacts of surface changes along 244 transects. The results demonstrate that coastal erosion is responsible for widespread and archaeologically significant damage, with 48% of the studied transects showing erosion during the period 1973–2016. We elucidate significant temporal variations in the data and, most notably, demonstrate that continued drought since the early 2000s has impacted upon sediment supply to coastal areas, severely accentuating erosion. For instance, between 2003 and 2016, 70% of transects recorded shoreline retreat with worrying implications for the waterfront archaeology of Siraf. These quantitative results provide invaluable spatial information regarding the causes and impacts of erosion upon Siraf's waterfront heritage, in addition to furnishing a template for the protection of the city's internationally important cultural heritage. Highlights: Successful heritage management requires understanding of the threats facing archaeological sites. We spatially quantify shoreline changes along the Siraf coastline between 1973 and 2016. 48% of the studied transects show erosion during the period 1973–2016, leading to widespread archaeological damage. We provide a template for the protection of Siraf's internationally important cultural héritage.